ANALISIS INVENTARISASI ASET TETAP PADA PEMERINTAH KABUPATEN BANTUL - , Hendro Novianto Sujarwo, Prof. Dr. Abdul Halim, MBA, Akt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fixed assets still became a factor of poor opinion on Local Government Financial Report (LKPD) throughout Indonesia. Bantul Regency Government in 2011 had conducted an inventory and audit of fixed assets. From LKPD in 2011, there was other post assets amounted to IDR 11,613,236,488.12, whereas this number derived from fixed assets of which properties details could not be traced. Based on this, it was assumed that the assets inventory and audit that had been carried was not in accordance with the conditions set. This research aimed to identify and analyze the essential of fixed assets inventory owned by Bantul Regency Government. The data were collected through questionnaires distribution using purposive sampling techniques and unstructured interviews were also conducted. To identify the factors, confirmatory factor analysis was used to analyze the results and identify the factors descriptive statistical analysis enriched with the data from the interviews result was used. The result of the factor analysis shows that there are five factors that underlie / explain the fixed asset inventory of Bantul Regency Government, namely: data collection factor, coding factor, grouping factor, recording factor and audit factor. Qualitative descriptive analysis result shows that the ability of information technology and the completeness of the infrastructure in the office have not been supported by the ability of the Human Resources, this is due to the inadequate knowledge of the properties managers concerning BMD management and the human resources managing BMD are less capable to operate the Computers. Besides, Bantul Regency Government has a database in the form of source book